2005
DOI: 10.7326/0003-4819-142-1-200501040-00008
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Acute Pyelonephritis in Healthy Women

Abstract: Few nonpregnant, community-dwelling women younger than 50 years of age with pyelonephritis are hospitalized. As with cystitis in reproductive-age women, sexual behaviors and patient and family history of UTI are associated with increased pyelonephritis risk. Diabetes and incontinence also seem to independently increase the risk for pyelonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
161
2
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(187 citation statements)
references
References 26 publications
(33 reference statements)
10
161
2
11
Order By: Relevance
“…We have shown before that only 0.5% of diabetic patients with a UTI had clinical symptoms of a pyelonephritis (17) compared with 0.2% in control subjects. Others have demonstrated that the risk ratio for pyelonephritis in patients with compared with those without diabetes ranges from 1.86 to 4.4 (18,19). These numbers make clear that even when more women with diabetes had clinical symptoms of a pyelonephritis and therefore were treated with norfloxacin during a longer period, this cannot totally explain the demonstrated differences.…”
Section: Secondary Analysesmentioning
confidence: 99%
“…We have shown before that only 0.5% of diabetic patients with a UTI had clinical symptoms of a pyelonephritis (17) compared with 0.2% in control subjects. Others have demonstrated that the risk ratio for pyelonephritis in patients with compared with those without diabetes ranges from 1.86 to 4.4 (18,19). These numbers make clear that even when more women with diabetes had clinical symptoms of a pyelonephritis and therefore were treated with norfloxacin during a longer period, this cannot totally explain the demonstrated differences.…”
Section: Secondary Analysesmentioning
confidence: 99%
“…MSK is found in 20% of patients with kidney stones and more than 70% of patients with MSK develop stones (7,9). Nephrolithiasis in MSK facilitates urinary tract infection (3).Dilatation of collecting tubules in MSK also plays role in recurrent pyelonephritis (10).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical anomalies such as vesicoureteral refl ux correlate strongly with acute pyelonephritis in children (Jantunen et al 2001;Lai and Ng 2003). In young or middleaged adults, acute pyelonephritis correlates with several well-known risk factors such as female gender, co-existing diabetes mellitus, pregnancy, urinary incontinence, sexual behavior and urolithiasis (Nicolle et al 1996;Hill et al 2005;Scholes et al 2005;Pertel and Haverstock 2006). In contrast, acute pyelonephritis has been relatively little evaluated in geriatric populations.…”
Section: Statistical Analysesmentioning
confidence: 99%